Leakage current conduction in metal gate junctionless nanowire transistors. (May 2017) - Oproglidis, T.A.; Karatsori, T.A.; Barraud, S.; Ghibaudo, G.; Dimitriadis, C.A.
Highlights: Off-state leakage current in metal gate junctionless nanowire transistors. The off-state leakage current is due to tunneling of carriers from silicon layer to metal gate. The conduction is due to trap-assisted Fowler-Nordheim tunneling mechanism. Abstract: In this paper, the experimental off-state drain leakage current behavior is systematically explored in n- and p-channel junctionless nanowire transistors with HfSiON/TiN/p + -polysilicon gate stack. The analysis of the drain leakage current is based on experimental data of the gate leakage current. It has been shown that the off-state drain leakage current in n-channel devices is negligible, whereas in p-channel devices it is significant and dramatically increases with drain voltage. The overall results indicate that the off-state drain leakage current in p-channel devices is mainly due to trap-assisted Fowler-Nordheim tunneling of electrons through the gate oxide of electrons from the metal gate to the silicon layer near the drain region.